Narratives of Mental Health in Modern Prose Literature - Maghfiroh, Diana (Politeknik Siber Cerdika Internasional, 2024)
This study examines the portrayal of mental health in modern prose literature, highlighting how contemporary narratives address the complexities of mental well-being and societal perceptions. Utilizing a qualitative methodology, this research conducts a thematic analysis of selected literary works published in the 21st century, focusing on the ways authors use narrative style, character development, and symbolic imagery to represent various mental health issues. By exploring characters’ internal struggles and their interactions within societal frameworks, this study investigates how these narratives contribute to the broader discourse on mental health, challenging stereotypes and promoting empathy. This analysis also considers the impact of cultural context on the depiction of mental health, analyzing how factors such as race, gender, and social class influence characters' experiences with mental illness. Through an in-depth examination of these texts, this research aims to contribute to a greater understanding of how literature not only mirrors societal attitudes but also actively shapes readers' awareness and empathy toward mental health. This study’s findings highlight the significant role of prose literature as a platform for social reflection and emotional engagement, suggesting that contemporary narratives can facilitate more compassionate perspectives on mental well-being.